The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2807/1560-7917.es.2017.22.28.30574
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of invasive meningococcal disease (IMD) caused by Neisseria meningitidis serogroup W among university students, France, February to May 2017

Abstract: Between February and May 2017, two cases of invasive meningococcal disease caused by a new, rapidly expanding serogroup W meningococci variant were reported among students of an international university in Paris. Bacteriological investigations showed that isolates shared identical genotypic formula (W:P1.5,2:F1–1:cc11) and belonged to the South American/UK lineage. A vaccination campaign was organised that aimed at preventing new cases linked to potential persistence of the circulation of the bacteria in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The ST-11 complex (cc11) is associated with outbreaks with high CFRs, atypical symptoms (e.g. gastrointestinal findings) and a variety of serogroups (MenC, MenW, and MenB) [55][56][57][58]. The spread of cc11 has been accompanied by capsule switching and antigenic shifts, and more recently, adaptation to new niches, e.g.…”
Section: Genomic Alterations and Epidemic Potential Of Neisseria Menimentioning
confidence: 99%
See 1 more Smart Citation
“…The ST-11 complex (cc11) is associated with outbreaks with high CFRs, atypical symptoms (e.g. gastrointestinal findings) and a variety of serogroups (MenC, MenW, and MenB) [55][56][57][58]. The spread of cc11 has been accompanied by capsule switching and antigenic shifts, and more recently, adaptation to new niches, e.g.…”
Section: Genomic Alterations and Epidemic Potential Of Neisseria Menimentioning
confidence: 99%
“…MenW cc11 isolates found in the U.K. from 2009 onwards, and associated with atypical symptoms (diarrhea, vomiting, and septic arthritis), likely originated from South America, having emerged in Brazil in 2003 before spreading to Argentina and Chile [37,52,61]. The U.K. strains have since been found in France, the Netherlands, Sweden, Australia, and Canada [42,43,51,54,55,63]. Further, within the cc11 population structure, MenB and MenC cc11 isolates were highly interspersed, suggesting multiple capsule switch events [37,62].…”
Section: Genomic Alterations and Epidemic Potential Of Neisseria Menimentioning
confidence: 99%
“…The sub-lineage consists of three strains: the South American strain, the original UK strain, and the UK 2013 strain (hereafter called the 2013 strain) [13,14]. An increase in NmW has been reported from several European countries [14][15][16][17], and in 2015, the 2013 strain was involved in an outbreak at an international scout jamboree in Japan, which resulted in invasive cases reported from Scotland and Sweden [13].…”
Section: Introductionmentioning
confidence: 99%
“…The study of these isolates by the whole genome sequencing (WGS) method revealed two genetically close lineages: one is linked to the Hajj 2000 epidemic and its subsequent spread throughout the world, including to South Africa, and the other is recently reported from Latin America, England, and other countries. The European isolates serogroup W cc11 of the latter lineage are classified into two sub-lineages: original UK strain and novel 2013 UK strain [4, 5, 6, 7, 8, 9, 10]. In 2015-2016, the resurgence of N. meningitidis W cc11 was reported in Madagascar.…”
Section: Introductionmentioning
confidence: 99%